A hollow core–shell structure material NiCo2S4@Ni2P with uniform heterojunction for efficient photocatalytic H2 evolution reaction. (20th November 2019) - Zhao, Sheng; Xu, Jing; Liu, Zeying; Li, Yanru
Abstract : Based on a bimetallic sulfide, a hollow core–shell structure material, NiCo2 S4 @Ni2 P, with a uniform type-I heterojunction achieved efficient photocatalytic H2 evolution. Abstract : A photocatalytic material, NiCo2 S4 @Ni2 P, with a unique hollow core–shell structure based on hollow spherical NiCo2 S4, which has a structure that is greatly advantageous for heterogeneous photocatalytic reactions, was successfully prepared. The unique hollow core–shell structure formed a homogeneous surface heterojunction, which caused the composite photocatalytic material to exhibit better photocatalytic HER activity and stability than the initial NiCo2 S4 in the dye-sensitized system. The photocatalytic HER rate of the optimal photocatalytic material, NiCo2 S4 @Ni2 P 10%, reached 77.97 μmol h −1 via the optimization of the photocatalytic H2 evolution performance. XRD and XPS were used to study the crystal structure and valence state of the photocatalytic material, respectively. Additionally, its morphology and structure were observed by SEM and TEM, respectively. The CB and VB potentials were derived by combining empirical formulas based on the UV-vis DRS data. Finally, the photocatalytic HER mechanism was investigated by photoelectrochemical and PL tests combined with the above data.